Estimation of carbon stock and economic value of Sanjiangyuan National Park, China - Weijing Ma; Shujuan Hou; Wufan Su; Ting Mao; Xiaoya Wang; Tingting Liang (Ecological Indicators)
Sanjiangyuan National Park (SNP) is one of China’s national parks with high ecological significance and ecological vulnerability. In order to promote the healthy development of national park ecosystems, it is extremely important to investigate the carbon sequestration potential and the economic value of carbon sequestration in the SNP. Here, we comprehensively analyzed the characteristics of land use change from 1985 to 2022 based on the land use transfer matrix and land use dynamic degree, calculated the ecosystem carbon storage based on the InVEST model, and estimated the economic value of carbon storage in each period combined with compound interest present value method. The results show that: (1) From 1985 to 2022, carbon stocks generally went through three phases: increasing, stabilizing, and decreasing. (2) Low carbon density areas were concentrated in the Kekexili Natural Reserve in the Yangtze River Source Park and a small part of the Yellow River Source Park and Lancang River Source Park; The high carbon density area was concentrated in the water area and the forest land in the southeast of the Lancang River Source Park. (3) Land use change in SNP had a decisive impact on carbon storage change, and the economic value of carbon storage in SNP continued to increase from 1985 to 2022. In order to provide a scientific basis for the sustainable management of carbon sinks and the reduction of carbon emissions in the SNP area, it is necessary to further study the carbon cycle process, carbon storage and carbon emissions in the region in the future.